Reduction of Construction Duration by Improving the Anti-Wear Properties of Power Fluids in Hydraulic Drives of Earth-Moving Machines - Voronin, Serhii; Onopreychuk, Dmytro; Stefanov, Volodymyr; Bashkatov, Yevhenii; Panchenko, Vitalii (International Journal of Engineering and Technology, 2018)
The structure of reduction of construction duration which takes into account the effect of the electrostatic field on the power fluid of a hydrostatic power drive of earth-moving machines is considered. Experimental studies are also considered that suggest that the exposure of the power fluid to an electrostatic field leads to the intensified formation and increased thickness and bearing capacity of the lubricant film on the friction surfaces of the hydraulic drive. This causes the reduced wear rate of the components of a hydrostatic power drive. In particular, gaps in plunger pairs in the pump are reduced, which contributes to the increase of the coefficient of performance. As a result, the operating speed of the driven equipment increases, i.e., the work cycle duration is reduced, and hence the capacity of earth-moving machines increases and the duration of the preparatory earthwork, which is about a quarter of the total duration of all construction works in general, is reduced.Â Â